Pengaruh Kebijakan Pajak dan Tingkat Inflasi Terhadap Pertumbuhan GDP (Gross Domestic Product)/ PDB (Produk Domestik Bruto): Tinjauan Literatur di Indonesia - Puput Iswandyah Raysharie; Alfina Rianti; Heberyani Br Tarigan; Ika Ayu Lestari; Irvina Rahimatullah Sofian; Meiyo Glori Tarigan; Tiara Saputri (Universitas Warmadewa, 2024)
The aims of research is to explore as well as analyze the impact of tax policy and inflation rates related to growth (GDP) in the context of a country's economy. The writing of this journal uses a Qualitative method, namely by using a literature study, which is often referred to as a literature review or literature review which is a systematic process of collecting, evaluating, and synthesizing existing information and knowledge in the form of journal articles, books, research reports, and other sources relevant to a particular research topic or problem. an increase in the tax rate can result in an increase in GDP because taxes collected by the government can be used to fund infrastructure projects or other public programs which in turn can encourage economic growth. The inflation rate can have a positive impact on GDP. In previous research, we can conclude that the effect of tax and inflation variables with Gross Domestic Product (GDP) has produced interesting findings that show a positive relationship between these variables and GDP. In this context, this positive effect indicates that an increase in tax and inflation rates can contribute to an increase in a country's GDP.